Conversations about adulthood recorded in the album "1-800 Enlightenment" by Taco Hemingway - rap as a learning space - Martyna Paulina Pryszmont (Studia z Teorii Wychowania)
Rap music is part of hiphop culture, and this music genre is has been developing in Poland since 1990s.The lyrics of rap songs are often biographical in nature, and their creators refer to their own experiences and experiences, which they describe and interpret, giving them subjective meaning. In this text, the author analyzed the work of Taco Hemingway - one of the most popular Polish rappers. She focused on the album titled “1-800 Enlightenment”, which tells the story of an artist overcoming a crisis and at the same time draws attention to the problems of adults. The main motive and message of the artist is to encourage people to talk about difficulties and problems, but also to reflect on their own lives. The author, referring to the biographical content contained in the artist’s album, analyzes the album in terms of its educational potential. It refers to the perspective of informal learning, and in particular to learning from one’s own biography and the biographies of others. The discussion on the artist’s album made it possible to describe rap as a space for adult learning.